K369I Tau Mice Demonstrate a Shift Towards Striatal Neuron Burst Firing and Goal-directed Behaviour. (21st November 2020) - Mo, Max; Jönsson, Marie E.; Mathews, Miranda A.; Johnstone, Daniel; Ke, Yazi D.; Ittner, Lars M.; Balleine, Bernard W.; Furlong, Teri M.; Camp, Aaron J.
Highlights: K3 transgenic mouse models the pathology of frontotemporal lobar degeneration. Discharge profile of neurons in the K3 striatum shifted towards burst firing. K3 striatal neurons show enhanced subthreshold activity. Altered medium spiny neurons in K3 mice show increased sensitivity. K3s have early deficits in goal directed behaviour attributed to striatal function. Abstract: Pathological forms of the microtubule-associated protein tau are involved in a large group of neurodegenerative diseases named tauopathies, including frontotemporal lobar degeneration (FTLD-tau). K369I mutant tau transgenic mice (K3 mice) recapitulate neural and behavioural symptoms of FTLD, including tau aggregates in the cortex, alterations to nigrostriatum, memory deficits and parkinsonism. The aim of this study was to further characterise the K3 mouse model by examining functional alterations to the striatum. Whole-cell patch-clamp electrophysiology was used to investigate the properties of striatal neurons in K3 mice and wildtype controls. Additionally, striatal-based instrumental learning tasks were conducted to assess goal-directed versus habitual behaviours (i.e., by examining sensitivity to outcome devaluation and progressive ratios). The K3 model demonstrated significant alterations in the discharge properties of striatal neurons relative to wildtype mice, which manifested as a shift in neuronal output towards a burst firing state. K3 mice acquired goal-directed responding faster than control mice and were goal-directed at test unlike wildtype mice, which is likely to indicate reduced capacity to develop habitual behaviour. The observed pattern of behaviour in K3 mice is suggestive of deficits in dorsal lateral striatal function and this was supported by our electrophysiological findings. Thus, both the electrophysiological and behavioural alterations indicate that K3 mice have early deficits in striatal function. This finding adds to the growing literature which indicate that the striatum is impacted in tau-related neuropathies such as FTLD, and further suggests that the K3 model is a unique mouse model for investigating FTLD especially with striatal involvement.